2023
DOI: 10.3390/jfb14020086
|View full text |Cite
|
Sign up to set email alerts
|

Silk–Inorganic Nanoparticle Hybrid Hydrogel as an Injectable Bone Repairing Biomaterial

Abstract: Silk fibroin is regarded as a promising biomaterial in various areas, including bone tissue regeneration. Herein, Laponite® (LAP), which can promote osteogenic differentiation, was introduced into regenerated silk fibroin (RSF) to prepare an RSF/LAP hybrid hydrogel. This thixotropic hydrogel is injectable during the operation process, which is favorable for repairing bone defects. Our previous work demonstrated that the RSF/LAP hydrogel greatly promoted the osteogenic differentiation of osteoblasts in vitro. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
(78 reference statements)
0
3
0
Order By: Relevance
“… Similarly, our research group, in collaboration with others, observed that SF/LAP hydrogels facilitated bone repair similarly and further identified that the inherent osteogenic properties of the RSF/LAP hybrid materials stemmed from the activation of the AKT pathway. This osteogenic effect was notably inhibited by an AKT pathway inhibitor, underscoring the critical role of AKT in the osteogenic capabilities of these materials …”
Section: Applications Of Sf-based 3d Porous Scaffolds In Tissue Engin...mentioning
confidence: 88%
See 1 more Smart Citation
“… Similarly, our research group, in collaboration with others, observed that SF/LAP hydrogels facilitated bone repair similarly and further identified that the inherent osteogenic properties of the RSF/LAP hybrid materials stemmed from the activation of the AKT pathway. This osteogenic effect was notably inhibited by an AKT pathway inhibitor, underscoring the critical role of AKT in the osteogenic capabilities of these materials …”
Section: Applications Of Sf-based 3d Porous Scaffolds In Tissue Engin...mentioning
confidence: 88%
“…This osteogenic effect was notably inhibited by an AKT pathway inhibitor, underscoring the critical role of AKT in the osteogenic capabilities of these materials. 78 Many researchers have also simulated the natural inorganic composition of bone by artificial means. For example, polyphosphate (CPP), calcium phosphate (OCP), biphasic calcium phosphate (BCP), and β-tricalcium phosphate (β-TCP) are commonly employed in bone repair and replacement.…”
Section: Applications Of Sf-based 3d Porous Scaffolds In Tissue Engin...mentioning
confidence: 99%
“…Roohaniesfahani et al incorporated MSM-10 ceramic particles into SF hydrogels by ultrasonic cross-linking, demonstrating that magnesium, strontium, and silicon ions released from MSM-10 ceramic particles increased the gelling time and silk I: silk II ratios in the secondary protein structure of SF hydrogels while improving the in vitro osteogenic properties of hydrogels [139]. Sun et al prepared RSF/LAP hydrogels for optimized bone repair [140]. According to previous studies [104], LAP in RSF hydrogels can either increase the number of β-sheet domains that act as hydrogel crosslinkers or limit their growth.…”
Section: Sf Hydrogels For Bonementioning
confidence: 99%